Efficient Discrete Interpolation Algorithm and Module Development of Cycloid Gear Profile - Yao Yuchao; Wang Qiliang; Chang Anquan; Jiang Zhongqiu (Jixie chuandong)
In view of the cycloid gear profile,an efficient discrete interpolation algorithm whose rotation angle intervals are auto adjusted by the curvature and errors are calculated by the numerical method is proposed. Based on this algorithm,a cycloidal tooth profile design module is developed. Meanwhile,the results of equal-pitch algorithm,equal-step algorithm,equal-error algorithm and this efficient discrete interpolation algorithm are compared which verified the feasibility and effectiveness of the method. Based on this design module,a data channel between discrete interpolation and engineering drawing software and 3D modeling software as well as the CNC machine tools is constructed.